Portable fresh coconut milk extractor for small and medium industries (SMI) / Ahmad Syahmi Yusneta - Yusneta, Ahmad Syahmi (2023)
A coconut milk extractor is a machine that extracts coconut milk from fresh coconuts. In today's world, it's becoming a viable alternative to the traditional extraction process. This approach is more dependable in terms of processing time, hygiene, and safety, and it needs fewer processing steps. The process of designing, fabricating, and analyzing a portable mockup model coconut milk extractor is presented in this thesis. Busy urban society, particularly working women, and Small and Medium Industries are the target population and prospective clients (SMI). The project's goal is to make a machine that is smaller and less expensive than those already in use in this sector. The machine prototype is built with material availability and fabrication utilities in mind. The prototype's final testing and performance, such as the amount of coconut milk that can be extracted and the prototype's efficiency, are measured. The design is believed to be able to extract a substantial volume of coconut milk while also acting as a user friendly kitchen gadget, therefore competing with other devices currently on the market.